The Patentability of Maori Traditional Medicine and the Morality Exclusion in the Patents Act 1953 - Young, Susan (Victoria University of Wellington Law Review, 2001)
Many indigenous peoples, including Maori, are offended by third parties ’appropriating’ their traditional knowledge by means of intellectual property rights, such as patents. The author first surveys international debate about indigenous intellectual property rights in connection with the patenting of traditional indigenous medicine. The author examines the role of morality in New Zealand patent law and how this fits in with New Zealand’s international obligations under the World Trade Organisation’s TRIPs agreement and the Convention on Biological Diversity. The author examines whether the patenting of Maori traditional medicine can be prevented under the morality exclusion in the Patents Act 1953 and outlines five arguments which might be used to justify various levels of intervention in the patenting process in order to protect Maori control over their traditional knowledge.